2017
DOI: 10.1136/tobaccocontrol-2016-053581
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use in restaurants and workplaces where combustible tobacco smoking is not allowed: an Internet survey in Japan

Abstract: Among adult Japanese e-cigarette ever-users, approximately 26%-29% had ever used and 16%-19% had frequently used e-cigarettes in restaurants and/or workplaces where combustible tobacco smoking is not allowed. Policy-makers may need to establish explicit rules as to e-cigarette use in smoke-free environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“… 1 32 33 Moreover, their actual health effects on users and their overall impact on public health are still not fully known. 34 Regulatory strategies for HNB tobacco should thus be carefully formulated with an eye towards the future. Regulators, however, are already far behind, because, as the present findings show, IQOS is already being widely used.…”
Section: Discussionmentioning
confidence: 99%
“… 1 32 33 Moreover, their actual health effects on users and their overall impact on public health are still not fully known. 34 Regulatory strategies for HNB tobacco should thus be carefully formulated with an eye towards the future. Regulators, however, are already far behind, because, as the present findings show, IQOS is already being widely used.…”
Section: Discussionmentioning
confidence: 99%
“…14 Another study conducted in 2015 in Japan on 1243 ever users showed that 29% had used electronic cigarettes in smoke-free restaurants and 26% in smoke-free workplaces. 40 A study from Australia in 2016 showed that among 66 current electronic cigarette users, 15% vaped in restaurants and bars and 28% in workplaces. 2 Finally, in a Spanish study based on 600 electronic cigarette users, 33% had used electronic cigarettes in workplaces, 69% in restaurants or bars, 3% on public transport, and 55% in nightclubs.…”
Section: Discussionmentioning
confidence: 99%
“…These figures are in broad agreement with the parallel prevalence of exposure to secondhand tobacco smoke (SHS) in these countries 18 . An internet survey conducted in Japan that analysed e-cigarette use in restaurants and workplaces reported that almost 30% of the respondents used e-cigarettes in smoke-free restaurants and about a quarter in smoke-free workplaces 19 . In five out of six countries in the current study the observed e-cigarette use is lower than that observed in Japan.…”
Section: Discussionmentioning
confidence: 99%